Francis of Assisi - Curtiz, Michael, 1886-1962.; Dillman, Bradford, 1930-2018.; Hart, Dolores, 1938-; De Wohl, Louis, 1903-1961.; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, Inc., 2004)
Francis Bernardone, son of a wealthy cloth merchant, after hearing the voice of Jesus speak to him, had a radical conversion from a worldly man of adventure to a life devoted to Christ lived in Gospel simplicity and service to the poor.
Originally produced as a motion picture in 1961.
Based on the novel by Louis de Wohl.
Bradford Dillman, Dolores Hart.
MPAA rating: Not rated.
DVD, widescreen presentation; Dolby Digital.
Closed-captioned
Keywords: Francis, -- of Assisi, Saint, -- 1182-1226 -- Drama; Christian saints -- Italy -- Assisi -- Drama; Video recordings for hard of hearing people; Assisi (Italy) -- Drama; Feature films